ANALYSIS OF THE APPLICATION OF PROJECT-BASED LEARNING MODEL BASED ON WORDWALL MEDIA IN GRADE 3 IPAS LEARNING - Rona Nabilatur Rofifah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study analyzes the implementation of a project-based learning (PjBL) model using Wordwall media in Grade 3 IPAS (Science) learning, focusing on data reduction, data presentation, and drawing conclusions. A descriptive qualitative approach was used at Fatimah Az Zahro Plus Elementary School, Buduran, Sidoarjo, with data collected through interviews, observations, and documentation. The findings revealed that: 1) Teachers in elementary schools are required to use various learning models, including PjBL; 2) The PjBL model in IPAS learning involves three stages: preparation of teaching modules, application of the PjBL model for processing natural resources material, and the evaluation stage; 3) The use of Wordwall media in the evaluation process enhances student engagement and creativity, making learning more interactive and enjoyable. Overall, the application of PjBL with Wordwall media promotes active student participation and reduces boredom in the learning process.